Cognitive Behavioral Therapy sebagai Strategi Layanan Bimbingan dan Konseling Kajian Teoretis Berbasis Literatur - Yuliana, Yuliana (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2026)
Cognitive Behavioral Therapy (CBT) is a psychological approach that emphasizes the interrelationship between thoughts, emotions, and behaviors in understanding and addressing individual problems. This approach is widely applied in educational settings due to its structured nature, goal-oriented focus, and emphasis on developing adaptive cognitive and behavioral skills. This article aims to examine the theoretical foundations and implementation of CBT in guidance and counseling services, both in individual and group counseling contexts. The novelty of this article lies in its interpretation of CBT not merely as a therapeutic approach, but also as a systematic and evidence-based guidance and counseling strategy to support students’ cognitive development, learning motivation, and psychological well-being. The research method employed is a literature review by analyzing various scientific sources, including journal articles, reference books, and supporting documents relevant to the implementation of CBT in guidance and counseling practices. The results of the review indicate that CBT is effective in enhancing learning and achievement motivation, reducing anxiety levels, and optimizing cognitive development through techniques such as cognitive restructuring, self-monitoring, problem solving, behavioral rehearsal, exposure, and homework assignments. The conclusion of this study confirms that CBT is a relevant and applicable approach in guidance and counseling services, with its effectiveness strongly influenced by counselor competence, active client involvement, and the structured and contextual implementation of counseling services.